Internal Economic Management and Performance Evaluation Method of Enterprise Based on Balanced Scorecard - Shuangshuang Liu (Discrete Dynamics in Nature and Society)
In order to evaluate the performance management level of the enterprise, it is necessary to use the Balanced Scorecard to establish the performance evaluation system of the enterprise. On the basis of pointing out the specific problems and deficiencies existing in the enterprise, suggestions for improving the performance level of the enterprise are put forward. Then, a detailed analysis of the performance evaluation of Company A is carried out. Through the analysis of various aspects of Company A’s performance, the problems and deficiencies in its performance evaluation are found. According to the specific problems of Company A, a performance evaluation system is designed based on the balanced scorecard. The Balanced Scorecard is a management tool for measuring performance in multiple dimensions. Starting from multiple aspects, scientifically combining strategic objectives with multiple dimensions, this management method not only is suitable for the current market environment, but also improves the company’s internal management system. Through the investigation of the company’s performance management, it is found that there is a problem in the company’s performance management. In view of the existing problems, the Balanced Scorecard of management accounting is used as a management tool to design a feasible performance appraisal plan for the company from the four dimensions of finance, customer, internal process, and learning and growth. Recommendations for full participation can be made for its implementation. The results show that the comprehensive score of Company A’s performance in 2022 is 70 points. It can be seen from the evaluation results that the financial performance evaluation level of the company is average. The company’s customer performance levels are average as well. The internal operation level of the enterprise is at a high level. The level of learning and growth performance of the business is very good. At the same time, according to the reliability test standard, the reliability coefficient of the questionnaire is 0.866, indicating that the reliability is acceptable.